Pendekatan Fuzzy Pada Peramalan Jumlah Kunjungan Wisatawan Mancanegara ke Kabupaten Badung - Oka, Tjokorda Bagus; Kencana, Eka N. (Jurnal Matematika; Vol 6 No 2 (2016)DO - 10.24843/JMAT.2016.v06.i02.p76, 2016)
This work is directed to forecast the number of foreign visitors come to tourist’s destinations at Badung regency, Province of Bali. Using visit historical data for period January 2000 to February 2015, Markov Transition Matrix and Fuzzy Triangular Number are applied to represent fuzzy logical relationship group and member function in fuzzy model, respectively.  The results showed the in-sample forecasting accuracy for our fuzzy model as much as 2,48 percent. To validate the model, we found the average forecasting error rate for five consecutive months (March – July 2015) as much as 2,70 percent.
Keywords: forecasting, fuzzy model, FTN, tourists’ visit, transition matrix